A series of dinuclear cuprous iodide complexes chelated with 1, 2-bis(diphenylphosphino)benzene derivatives: structural, photophysical and thermal properties. Issue 23 (6th April 2016) - Li, Xiaoyue; Zhang, Juanye; Wei, Feng; Liu, Xiaochen; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : Three new bisphosphine ligands, Ph-dppd, Pr-dppb, and OMe-dppb, were synthesized to coordinate with cuprous iodide (CuI), and compared with dppb. Abstract : Three new bisphosphine ligands, 4-phenyl-1, 2-bis(diphenylphosphino)benzene (Ph-dppb), 4-pyrrolyl-1, 2-bis(diphenylphosphino)benzene (Pr-dppb), and 4, 5-dimethoxyl-1, 2-bis(diphenylphosphino)benzene (OMe-dppb), were synthesized to coordinate with cuprous iodide (CuI), and compared with 1, 2-bis(diphenylphosphino)benzene (dppb). Single crystal X-ray diffraction and elemental analysis experiments indicate that three binuclear CuI complexes with formulae of [Cu(μ2 -I)Ph-dppb]2, [Cu(μ2 -I)Pr-dppb]2, and [Cu(μ2 -I)OMe-dppb]2 were obtained, which are the same as the reference complex [Cu(μ2 -I)dppb]2 . The three complexes showed a maximum emission band ( λ max ) in the range of 484–535 nm which varies in the electron effect of the substituted groups ( i.e. methoxy, pyrrolyl, phenyl) on [Cu(μ2 -I)dppb]2, and in high photoluminescence quantum yield (PLQY) from 53 to 90% in the solid state. Furthermore, the complexes [Cu(μ2 -I)Ph-dppb]2 and [Cu(μ2 -I)Pr-dppb]2 exhibited a thermal decomposition temperature exceeding 380 °C. The high PLQY and excellent thermal stability of these CuI complexes imply their great potential application as efficient emitters in organic light-emitting diodes (OLEDs).